Synthesis of potassium niobates by the microwave-assisted solvothermal method - Duarte, T. M.; Honorio, L. M.C.; Brito, A. S.; Souza, J. K.D.; Longo, E. [UNESP]; Tranquilin, R. L.; Souza, A. G.; Santos, I. M.G.; Maia, A. S. (My University, 2015)
Potassium niobates have been synthesized by different methods, but few papers use the microwave-assisted solvothermal method, with possibility of a deeper evaluation in this area. In this work, the synthesis of KNbO3, KNb3O8 and K4Nb6O17 was performed by calcinations of precursors obtained by the microwave-assisted solvothermal method. This study evaluates the influence of various synthesis parameters such as reaction time, pH of the reaction medium, K+ concentration in the precursor solution. The results show the formation of different niobates, KNbO3, KNb3O8, K4Nb6O17, depending on the short and long-range order of the precursor used in the post annealing process.